2-Chloro-6,6-dimethyl-5,6-dihydroindazolo[2,3-c]quinazoline - Boechat, N.; Lages, A.S.; Kover, W.B.; Tiekink, E.R.T.; Wardell, J.L.; Wardell, S.M.S.V. (International Union of Crystallography, 2010)
Two independent but virtually identical molecules comprise the asymmetric unit of the title compound, C16H14ClN3. The molecules have a slightly curved shape owing to puckering in the six-membered C4N2 ring; the respective dihedral angles formed between the benzene rings are 12.64 (7) and 11.72 (7)degrees. In the crystal, layers sustained by a combination of N-H center dot center dot center dot N hydrogen bonding as well as C-H center dot center dot center dot N and C-H center dot center dot center dot pi contacts are formed; these stack along [011] and are connected by further C-H center dot center dot center dot pi contacts.